Association between loneliness and dementia risk: A systematic review and meta-analysis of cohort studies - Qiao, Luyao; Wang, Gege; Tang, Zhenyu; Zhou, Siqi; Min, Jun; Yin, Min; Li, Min (Frontiers in Human Neuroscience, 2022)
Loneliness has been reported to be associated with an increased risk of dementia; however, the extent of this relationship remains controversial. This study aimed to assess the strength of the relationship between loneliness and dementia using a meta-analysis approach. PubMed, EMBASE, and China National Knowledge Internet databases were systematically searched for potentially included studies from inception up to February 17, 2022. A meta-analysis was performed using a random-effects model to assess pooled relative risks (RRs) and 95% confidence intervals (CIs). A literature search identified sixteen cohort studies (published in fifteen articles), among which 4,625 dementia cases and 62,345 individuals were selected for further meta-analysis. Loneliness was associated with an increased risk of Alzheimer's disease (RR: 1.72, 95% CI: 1.32–2.23; P < 0.001) and dementia (RR: 1.23, 95% CI: 1.16–1.31; P < 0.00001). However, no significant association between loneliness and risk of mild cognitive impairment (RR: 1.34, 95% CI: 0.97–1.87; P = 0.080) or vascular dementia (RR: 1.01, 95% CI: 0.51–1.99; P = 0.973) was observed. Results revealed that loneliness might increase the risk of Alzheimer's disease and dementia. Early interventions that limit loneliness may reduce risk of dementia and Alzheimer’s disease.